Immunogenicity and efficacy of an oral live-attenuated vaccine for bovine Johne’s disease - Eshraghisamani, Razieh; Facciuolo, Antonio; Harman-McKenna, Victoria; Illanes, Oscar; De Buck, Jeroen (Frontiers in Immunology, 2024)
Mycobacterium avium subsp. paratuberculosis (MAP), the etiological agent of Johne's disease (JD) in ruminants, establishes a prolonged and often lifelong enteric infection. The implementation of control measures for bovine JD has faced obstacles due to the considerable expenses involved in disease surveillance and hindered by unreliable and inadequate diagnostic tests, emphasizing the need for an effective vaccine that can stimulate mucosal immunity in the gastrointestinal tract. Previous investigations have demonstrated that deletion of the BacA gene in MAP produces an attenuated strain that can transiently colonize the calf small intestine while retaining its capacity to stimulate systemic immune responses similar to wildtype MAP strains. This study assessed the efficacy of the BacA gene deletion MAP strain, referred to as the BacA vaccine, when administered orally to young calves. The research aimed to evaluate its effectiveness in controlling MAP intestinal infection and to investigate the immune responses elicited by mucosal vaccination. The study represents the first evaluation of an enteric modified live MAP vaccine in the context of an oral MAP challenge in young calves.Oral immunization with BacA reduced MAP colonization specifically in the ileum and ileocecal valve. This partially protective immune response was associated with an increased frequency of CD4+ and CD8+ T cells with a pro-inflammatory phenotype (IFN+/ TNF+) in vaccinated animals. Moreover, re-stimulated PBMCs from vaccinated animals showed increased expression of IFN, IP-10, IL-2, and IL-17 at 10-and 12-weeks post challenge. Furthermore, immunophenotyping of blood leukocytes revealed that vaccinated calves had increased levels of T cells expressing cell-surface markers consistent with long-term central memory.Overall, our findings provide new insights into the development and immunogenicity of a modified live MAP vaccine against bovine JD, demonstrating oral vaccination can stimulate host immune responses that can be protective against enteric MAP infection.